Impact of National Quality Infrastructure Development on Export Performance in Sri Lanka - Bandara, Willora Mudiyanselage Dulanjali Upamalika; Intarakumnerd, Patarapong (National Research and Innovation Agency, Indonesia, 2024)
This study examines the impact of National Quality Infrastructure (NQI) development on Sri Lanka’s export performance from the perspectives of Sri Lankan exporters, addressing a gap in the existing literature. Using a mixed-methods approach, this research integrates secondary data analysis, surveys of export-oriented businesses, and sector-specific case studies. Findings reveal a positive correlation between Quality Infrastructure for Sustainable Development (QI4SD) and export performance in countries such as China, Japan, and South Korea; however, moderate outcomes in Singapore and India suggest additional influencing factors. Survey data indicate that exporters employ Metrology, Standards, Testing, and Quality (MSTQ) frameworks to enhance productivity and product quality. Sector-specific case studies highlight distinct priorities, with edible goods exporters focusing on hygiene and safety standards, and non-edible goods exporters prioritizing efficiency and consistency. Despite MSTQ adoption, exporters encounter persistent challenges such as financial constraints and trade barriers. The study concludes with policy recommendations to improve knowledge dissemination, expand financial support, address import restrictions through collaborative policies, and enhance participation in Free Trade Agreements. These measures are crucial for fostering sustainable growth in Sri Lanka’s export sector.